Karakteristik Sensori dan Kandungan Gizi Es Krim Berbasis Tepung Pisang Kepok dan Tepung Kulit Pisang Kepok dengan Penambahan Bunga Telang dan Daun Kelor sebagai Alternatif Cemilan Penderita Diabetes: Sensory Characteristics and Nutritional Content of Ice Cream Based on Kepok Banana Flour and Kepok Banana Peel Flour with the Addition of Butterfly Pea Flowers and Moringa Leaves as an Alternative Snack for Diabetic Patients - Monicha, Miranda; Yunieswati, Wilda (Departemen Gizi Masyarakat, Fakultas Ekologi Manusia, IPB dan PERGIZI PANGAN Indonesia, 2023)
Diabetes mellitus is a condition where blood sugar levels become high due to insulin deficiency or resistance. One way to control blood sugar levels is to eat foods low in sugar and carbohydrates. An alternative to ice cream with a low-sugar formulation or using natural ingredients with anti-diabetic activity can be a suitable product for consumption by diabeticians. Several ingredients have antidiabetic activity, including bananas, butterfly pea flowers, and Moringa leaves. The research aims to determine the sensory quality characteristics and nutritional content of ice cream products. The experimental study used a completely randomized design (CRD). The design consisted of 3 treatments with the ratio F1 (100% kepok banana flour:0% kepok banana peel flour), F2 (95% kepok banana flour:5% kepok banana peel flour), and F3 (90% kepok banana flour:10% kepok banana peel flour). The statistical test used the Kruskal Wallis test and the follow-up test used the Mann Whitney The best formula was selected, namely F3 which had hedonic qualities namely brownish gray, slightly fragrant banana aroma, soft texture, sweet taste, and slightly bitter aftertaste. The hedonic test shows results in the range of 3-4 (normal-rather like). The energy content of F3 ice cream is 106 kcal/100g, 5.84 grams of carbohydrates, 0.17 g of fat, 0.32 g of protein and 38,863.21 ppm of antioxidant activity.